2019
DOI: 10.1021/acs.est.9b00259
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Long-Term Toxicity of Triclosan to Freshwater Green Algae in Lake Erie

Abstract: This study explored the long-term impacts of a pulse disturbance of triclosan on five nontarget green algae in Lake Erie. Comprehensive analyses were performed using multiple physiological end points at community and subcellular scales. The toxic mechanism of triclosan in a wide range of concentrations was analyzed. The diverse sensitivity of algae species and complex interrelationships among multiple end points were revealed. The results showed the taxonomic groups of algae were the key issue for sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 69 publications
0
19
2
Order By: Relevance
“…Daphnia or water flea is a freshwater planktonic crustacean often found pelagic, predatorily by fish while algae are primary producers in the ecosystem and their photosynthetic machinery has been reported to be adversely affected by TCS (Eriksson et al 2015). The loss of the photosynthetic ability of the algae following exposure to TCS may lead to acidification of the river water (Xin et al 2019) as the result of CO 2 build-up. TCS induced concentration-dependent Wang et al 2013Shen et al 2012Loraine and Pettigrove 2006Kolpin et al 2002 nd, not detected genotoxicity has also been reported in certain species of algae namely Asterococcus superbus and Chlamydomonas reinhardtii (Xin et al 2019) which abound in freshwater such as the Buffalo River.…”
Section: Ecological Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Daphnia or water flea is a freshwater planktonic crustacean often found pelagic, predatorily by fish while algae are primary producers in the ecosystem and their photosynthetic machinery has been reported to be adversely affected by TCS (Eriksson et al 2015). The loss of the photosynthetic ability of the algae following exposure to TCS may lead to acidification of the river water (Xin et al 2019) as the result of CO 2 build-up. TCS induced concentration-dependent Wang et al 2013Shen et al 2012Loraine and Pettigrove 2006Kolpin et al 2002 nd, not detected genotoxicity has also been reported in certain species of algae namely Asterococcus superbus and Chlamydomonas reinhardtii (Xin et al 2019) which abound in freshwater such as the Buffalo River.…”
Section: Ecological Risk Assessmentmentioning
confidence: 99%
“…The loss of the photosynthetic ability of the algae following exposure to TCS may lead to acidification of the river water (Xin et al 2019) as the result of CO 2 build-up. TCS induced concentration-dependent Wang et al 2013Shen et al 2012Loraine and Pettigrove 2006Kolpin et al 2002 nd, not detected genotoxicity has also been reported in certain species of algae namely Asterococcus superbus and Chlamydomonas reinhardtii (Xin et al 2019) which abound in freshwater such as the Buffalo River. These instances are capable of producing a negative shift in the balance of the ecosystem.…”
Section: Ecological Risk Assessmentmentioning
confidence: 99%
“…TCS toxicity studies with diverse algae (not including P. subcapitata) are reported (Ciniglia et al, 2005;Almeida et al, 2017;Xin et al, 2019a). This biocide promotes the reduction of chlorophyll concentration (Pan et al, 2018;Wang et al, 2020), perturbs photosynthesis (Ciniglia et al, 2005;Xin et al, 2019a) and increases membrane permeability (González-Pleiter et al, 2017;Wang et al, 2020). In addition to these effects, a reduction of algal biovolumes/size was reported for several spherical algae (Xin et al, 2017(Xin et al, , 2019a.…”
Section: Introductionmentioning
confidence: 99%
“…This biocide promotes the reduction of chlorophyll concentration (Pan et al, 2018;Wang et al, 2020), perturbs photosynthesis (Ciniglia et al, 2005;Xin et al, 2019a) and increases membrane permeability (González-Pleiter et al, 2017;Wang et al, 2020). In addition to these effects, a reduction of algal biovolumes/size was reported for several spherical algae (Xin et al, 2017(Xin et al, , 2019a. Due to its high sensitivity and the unawareness of the toxic effects promoted by this biocide on P. subcapitata, this alga appears as a good aquatic model organism, of lower trophic level, to be used in the elucidation of the TCS mechanisms of toxicity, on non-target organisms.…”
Section: Introductionmentioning
confidence: 99%
“…If the lake at Baysh Dam start to develop such harmful algae colonies on its surface in the presence of sunlight and shortage of rainfalls, the developing of harmful algae could be uncontrolled and pollutes the soil and ground water [9].…”
Section: Introductionmentioning
confidence: 99%